HOLOCENE PALAEOCLIMATE RECONSTRUCTIONS AT VANNDALSVATNET, WESTERN NORWAY, WITH PARTICULAR REFERENCE TO THE 8200 CAL. YR BP EVENT - Nesje A.; Bjune A.E.; Bakke J.; Dahl S.O.; Lie O.; Birks H.J.B. (My University, 2006)
Analyses of organic content, magnetic susceptibility, grain size and pollen in sediments from the proglacial lake Vanndalsvatnet in western Norway provide a high-resolution terrestrial record and pollen-based quantitative estimates of mean July and January temperatures and annual precipitation across the ? 8200 cal. yr BP event. Glaciers in the catchment melted away at approximately 8600 cal. yr BP. Immediately following deglaciation, a series of thin minerogenic layers indicate several abrupt, short-lived glacial episodes peaking at ? 8550, 8450, 8350, 8250, 8200, 7900, 7300 and 7150 cal. yr BP. A single, mid-Holocene glacial episode occurred at 4900-4800 cal. yr BP. Between 2000 and 1400 cal. yr BP, six short-lived glacial episodes occurred ? 2000, 1900, 1800, 1700, 1600, and 1500 cal. yr BP. The part of SpOrteggbreen that drains to Vanndalsvatnet has existed continuously since ? 1400 cal. yr BP. Just prior to a first loss-on-ignition minimum reflecting a glacial episode centred at 8200 cal. yr BP, pollen-inferred July temperatures were relatively high, January temperatures were low, and annual precipitation was relatively low. During the period 8200-7900 cal. yr BP, July temperatures showed a falling trend. Both January temperature and annual precipitation, however, were relatively high. After 7900 cal. yr BP, July temperatures increased, but both January temperatures and annual precipitation were lower than in the preceding period. The pollen analytical and sedimentary data suggest that the glacial advance during the Finse event seems not to have been a response to cooler summers, but to milder winters and increasing precipitation (similar to a positive North Atlantic Oscillation weather mode).
Keywords: 8200 CAL. YR BP EVENT; FINSE EVENT; LAKE SEDIMENTS; WESTERN NORWAY; POLLEN-CLIMATE RELATIONSHIPS; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен